2021
DOI: 10.1371/journal.ppat.1009634
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and coronavirus (SARS-CoV-2): Molecular mechanism of Metformin intervention and the scientific basis of drug repurposing

Abstract: Coronavirus Disease 2019 (COVID-19), caused by a new strain of coronavirus called Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), was declared a pandemic by WHO on March 11, 2020. Soon after its emergence in late December 2019, it was noticed that diabetic individuals were at an increased risk of COVID-19–associated complications, ICU admissions, and mortality. Maintaining proper blood glucose levels using insulin and/or other oral antidiabetic drugs (such as Metformin) reduced the detrimental ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 124 publications
(199 reference statements)
1
56
0
2
Order By: Relevance
“…Studies also show that SARS-CoV-2 can gain entry into endothelial cells via the endothelial cell surface ACE2 receptors [12][13][14]. Another study reported a different mechanism for impaired endothelial function.…”
Section: Evidence Of Ace2 and Tmprss2 On Pancreatic Beta Cellsmentioning
confidence: 97%
“…Studies also show that SARS-CoV-2 can gain entry into endothelial cells via the endothelial cell surface ACE2 receptors [12][13][14]. Another study reported a different mechanism for impaired endothelial function.…”
Section: Evidence Of Ace2 and Tmprss2 On Pancreatic Beta Cellsmentioning
confidence: 97%
“…Currently, metformin is gaining huge attention as a repurposed drug, as analyses of clinical data revealed reduced mortality rates of COVID-19 patients who had been treated with the anti-diabetic drug (Crouse et al, 2021;Ibrahim et al, 2021;Varghese et al, 2021). These findings suggest an urgent need of large clinical trials with metformin as prophylactic intervention for immune aging and ageassociated diseases.…”
Section: Autophagy Induction By Rapamycinmentioning
confidence: 99%
“…Patients who used metformin before hospitalization also showed lower severity parameters at admission 293 . During SARS-CoV-2 infection, in addition to controlling the glucose level, metformin may attenuate ED, inhibit viral entry and infection, resist oxidative stress, and change inflammatory and immune responses that would explain its ability to achieve cardiovascular protection in COVID-19 294 , 295 . Therefore, metformin may represent a drug candidate for treating COVID-19 and gain the advantage of fighting SARS-CoV-2 induced immune storm in COVID-19 patients with diabetes 296 .…”
Section: Future Directionsmentioning
confidence: 99%